2014
DOI: 10.1134/s0020168514080056
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of thin SiO2-P2O5-CaO films

Abstract: Thin SiO 2 -P 2 O 5 -CaO films have been produced by a sol-gel process from film forming solu tions. The physicochemical processes underlying the formation of the films have been investigated, and their phase composition, structure, and bioactivity have been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…Orientational interactions prevail for the studied solutions during the first 3 days, so the viscosity of the solutions increases sharply on the second day and decreases on the next day. Subsequently, a new structure is formed in the solutions due to the processes of orientational polarization during the electrostatic interaction of dissolved substances with each other and alcohol molecules. ,− In the case of a high concentration of phosphoric acid, spatial difficulties are of little importance compared to its catalyzing action, and as a consequence, there is a sharp increase in viscosity at relatively early stages of solution maturation and gelation in the solution.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orientational interactions prevail for the studied solutions during the first 3 days, so the viscosity of the solutions increases sharply on the second day and decreases on the next day. Subsequently, a new structure is formed in the solutions due to the processes of orientational polarization during the electrostatic interaction of dissolved substances with each other and alcohol molecules. ,− In the case of a high concentration of phosphoric acid, spatial difficulties are of little importance compared to its catalyzing action, and as a consequence, there is a sharp increase in viscosity at relatively early stages of solution maturation and gelation in the solution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In a previous work, the acid−base properties of the surface of the samples dried at 60 °C and annealed at 600 and 800 °C were studied to determine the surface charge of the material. 45 Changing the pH of the suspension of samples dried at 60 °C was due to the dissolution of calcium ions as they were still part of the soluble nitrates. Since the calcium ion exhibited strong basic properties, the pH of the sample suspension was weakly acidic (pH = 6).…”
Section: Composition and Properties Of Aggregatively Stablementioning
confidence: 99%
“…Dried FFS at 60 °C were studied by IR spectroscopy ( [7,12] is formed during reactions of hydrolysis and condensation of tetraethoxysilane..…”
Section: Resultsmentioning
confidence: 99%
“…A necessary condition for bone tissue regeneration -is opportunity to form a calcium phosphate layer on the surface of material [6]. Еarlier work [7] it was found that the presence of silica in the system contributes to obtaining a uniform film with good adhesion Introduction of titanium dioxide in the system increases the bioactivity of the implant, as on the material surface in addition to bonds Si -OH present bonds Ti -OH [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…According to data [7], for obtaining calcium phosphate materials on titanium substrates are widely used of sol-gel method. Using the sol-gel method in the preparation of calcium phosphate coating on a substrate allows improve the bioactivity titanium implant by changes the surface and the micro and nanotopographic characteristics.…”
Section: Introductionmentioning
confidence: 99%